2022
DOI: 10.3389/fspor.2022.854614
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Performance in Competitive Ski Mountaineering: An Inertial Sensor Case Study

Abstract: Organized biannually in the Swiss Alps since 1984, the “Patrouille des Glaciers” (PDG) is one of the most challenging long-distance ski mountaineering (skimo) team competitions in the world. The race begins in Zermatt (1,616 m) and ends in Verbier (1,520 m), covering a total distance of 53 km with a cumulated 4,386 m of ascent and 4,482 m of descent. About 4,800 athletes take part in this competition, in teams of three. We hereby present the performance analysis of the uphill parts of this race of a member (#1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…While racing strives for optimizing performance combined with light equipment ( Bortolan et al, 2021 ), as a recreational sport, skimo combines alpine and Nordic skiing characteristics and provides the chance for skiers to enjoy the outdoors in a unique and adventurous way. The physiological strain of skimo can be high, and racing was described as one of the most strenuous endurance sports ( Duc et al, 2011 ; Praz et al, 2014 ; Lasshofer et al, 2021 ; Kayser and Mariani, 2022 ), with high relevance of performance testing and analysis ( Menz et al, 2021 ; Schöffl et al, 2022 ; Zimmermann et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…While racing strives for optimizing performance combined with light equipment ( Bortolan et al, 2021 ), as a recreational sport, skimo combines alpine and Nordic skiing characteristics and provides the chance for skiers to enjoy the outdoors in a unique and adventurous way. The physiological strain of skimo can be high, and racing was described as one of the most strenuous endurance sports ( Duc et al, 2011 ; Praz et al, 2014 ; Lasshofer et al, 2021 ; Kayser and Mariani, 2022 ), with high relevance of performance testing and analysis ( Menz et al, 2021 ; Schöffl et al, 2022 ; Zimmermann et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…But no power data is presented or discussed. Recently, Kayser and Mariani (2022) present the performance analysis of the uphill sections of a long-distance SkiMo team competition. Power values from 237 to 321 W are just presented but not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Current Issues in Sport Science, 9(3), Article 005. https://doi.org/10.36950/2024.3ciss005 Ski mountaineering (skimo) is a popular outdoor activity that combines skiing and mountaineering, allowing skiers to explore backcountry terrain that is usually inaccessible by lift systems. Ski mountaineers often encounter steep and challenging terrain that requires adjustments to their equipment to optimize performance and safety (Fornasiero et al, 2018;Kayser & Mariani, 2022). One of the key components of skimo equipment is the binding, which connects the skier's boot to the ski.…”
mentioning
confidence: 99%
“…Recreational skimo is a strenuous endurance exercise which places high importance on comfort and efficiency to sustain this endurance exercise (Praz et al, 2016a). Previous research has shown that in skimo competitions, skiers maintain 80% heart rate max (HRmax) during skimo races (Kayser & Mariani, 2022).…”
mentioning
confidence: 99%